Δ13C compound-specific isotope analysis in organic compounds by GC/MC-ICPMS. Issue 9 (22nd July 2021) - Zakon, Yevgeni; Halicz, Ludwik; Gelman, Faina
Abstract : The work demonstrates a novel analytical method for compound-specific carbon isotope analysis in organic compounds by gas chromatography hyphenated with MC-ICPMS. Abstract : The work demonstrates a novel analytical method for compound-specific carbon isotope analysis in organic compounds by gas chromatography hyphenated with MC-ICPMS. Precision down to 0.3‰ (1 σ ) was attained for analytes containing as low as 0.6 nmol of carbon. Tuning of MC-ICPMS was performed on the background signals for m / z 12 and m / z 13. MC-ICPMS was operated in a low-resolution mode ( m /Δ m ∼ 300) and the instrumental parameters were optimized for the minimum m / z 13 to m / z 12 ratio. Good agreement between the δ 13 C values measured for ethylene dibromide, 2-chloroethyl benzene and naphthalene by GC/MC-ICPMS and the values determined for these compounds by GC-C-IRMS was observed. Determination of the carbon isotope ratio in the VPDB scale, as well as the absolute 13 C/ 12 C values was performed by applying an internal standard with known carbon isotope ratio.